KEBIASAAN MAKAN MUDSKIPPER Boleophthalmus pectinirostris (Linnaeus, 1758) DI MUARA SUNGAI MARO KABUPATEN MERAUKE, PAPUA - Sunarni Sunarni; Sisca Elviana (Musamus Fisheries and Marine Journal, 2019)
Food is one of the most important factors for fish. Food determines the extent of spread a types and can controlthe size of a population. Informations about feeding habits from mudskipper (B. Pectinirostris) is still verylimited, especially in the mouth of the Maro estuary, Merauke district, Papua. The purpose of this study is toexamine the feeding habits of mudskipper (B. Pectinirostris). Based on the analysis of Mudskipper's (B.pectinirostris) feeding habits which were found during the study consisted of 2 food types, namelyphytoplankton and mollusca. The main types of food Mudskipper (B. pectinirostris) is Rhizosolenia Hebetatafrom the Phytoplankton. Keywords: Mudskipper; Feeding habits; Maro Estuary